Efficient, stable, and reusable silicoaluminophosphate for the one-pot production of furfural from hemicellulose - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (ACS Catalysis, 2013)
Development of stable, reusable, and water tolerant solid acid catalysts in the conversion of polysaccharides to give value-added chemicals is vital because catalysts are prone to undergo morphological changes during the reactions With the anticipation that silicoaluminophosphate (SAPO) catalysts will have higher hydrothermal stability, those were synthesized, characterized, and employed in a one-pot conversion of hemicellulose. SAPO-44 catalyst at 170 degrees C within 8 h could give 63% furfural yield with 88% mass balance and showed similar activity up to at least 8 catalytic cycles. The morphological studies revealed that SAPO catalysts having hydrophilic characteristics are stable under reaction conditions.
Keywords: furfural; Hemicellulose; hydrophilicity; SAPO; water-tolerant catalyst; zeolite

Exceptionally high yields of furfural from assorted raw biomass over solid acids - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (RSC Advances, 2014)
Development of stable and recyclable solid acid catalysts in the efficient valorisation of hemicellulose to yield C-5 sugars and furfural is vital to boost the prospects of using lignocelluloses for chemicals synthesis. Using an silicoaluminophosphate, namely SAPO-44, as a catalyst, an environmentally benign process of furfural synthesis from diversified real substrates (without any treatment or the need for separation of its components) is shown. In an efficient one-pot methodology, at 443 K and in the presence of a biphasic solvent system, selective conversions of hemicelluloses from raw biomass (bagasse, rice husk and wheat straw) to extraordinarily high yields of furfural of about 93% were attainable. Under similar reaction conditions, an 82% yield of furfural is also achievable directly from isolated hemicellulose within 10 h. Hydrophilic SAPO-44, having higher hydrothermal stability, showed similar activity for all the substrates for a minimum of up to 8 times in recycling runs. Various physicochemical characterizations (X-ray diffraction, thermogravimetric analysis-derivative thermogravimetry, temperature programmed desorption-NH3, N-2 sorption, solid-state nuclear magnetic resonance spectroscopy) of fresh and spent catalysts were used to improve SAPO-44 stability.

Effects of careful designing of SAPO-44 catalysts on the efficient synthesis of furfural - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (Catalysis Today, 2015)
Considering the growing importance of furfural, it is necessary to develop a robust solid acid catalyst for the conversion of xylan (hemicelluloses) into furfural in a one-pot method. In this study, the effects of various components (Si, Al and P) and crystallization time on the preparation of acidic materials and their properties are extensively described. It is seen that with the increase in crystallization time (0, 48, 96, 176 h) during the synthesis of silicoaluminophosphate (SAPO-44), materials morphology changes from amorphous to AFI to CHA and the best activity for furfural synthesis (82%) from xylan was observed with SAPO-44 catalyst aged for 176 h. Since, acidity in the SAPO-44 is guided by the incorporation of Si in the ALPO framework, study on Si molar concentration (0.8, 1.0, 1.2, 1.4 and 1.6) in SAPO-44 was carried out and it was observed that SAPO-44 having 1.0 mole of Si content is the best catalyst for the xylan/xylose conversion to furfural. Catalyst structure-activity correlation is thoroughly defined with the help of several physico-chemical properties. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomass; furfural; Hemicellulose; SAPO-44; Xylose

Efficient method for the conversion of agricultural waste into sugar alcohols over supported bimetallic catalysts - Tathod, Anup P.; Dhepe, Paresh Laxmikant (Bioresource Technology, 2015)
Promoter effect of Sn in the PtSn/gamma-Al2O3 (AL) and PtSn/C bimetallic catalysts is studied for the conversion of variety of substrates such as, C5 sugars (xylose, arabinose), C6 sugars (glucose, fructose, galactose), hemicelluloses (xylan, arabinogalactan), inulin and agricultural wastes (bagasse, rice husk, wheat straw) into sugar alcohols (sorbitol, mannitol, xylitol, arabitol, galactitol). In all the reactions, PtSn/AL showed enhanced yields of sugar alcohols by 1.5-3 times than Pt/AL. Compared to C, AL supported bimetallic catalysts showed prominent enhancement in the yields of sugar alcohols. Bimetallic catalysts characterized by X-ray diffraction study revealed the stability of catalyst and absence of alloy formation thereby indicating that Pt and Sn are present as individual particles in PtSn/AL. The TEM analysis also confirmed stability of the catalysts and XPS study disclosed formation of electron deficient Sn species which helps in polarizing carbonyl bond to achieve enhanced hydrogenation activity. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Agricultural waste; Bimetallic catalyst; Hydrogenation; Monosaccharides; Polysaccharides

Efficient hydrogenation of concentrated aqueous furfural solutions in to furfuryl alcohol under ambient conditions in presence of PtCo bimetallic catalysts - Dohade, Manisha; Dhepe, Paresh Laxmikant (Green Chemistry, 2017)
Furfural (FAL), a major biomass-derived chemical, can be hydrogenated to yield the industrially importantplatform chemical, furfuryl alcohol (FOL). Although heterogeneous catalyst-based methods are known toyield FOL from dilute solutions of FAL, they mainly operate at high temperatures and/or high pressures ofhydrogen and in the presence of organic solvents. In this work, we employ bimetallic PtCo/C catalysts withvarying metal concentrations to achieve the maximum possible FOL yield (100%) at 35 °C under 0.1 MPa H2in water. With concentrated FAL (40 wt%) at 50 °C and under 1 MPa H2pressure, 86% yield of FOL wasobserved. Moreover, eﬃcient catalyst recycling was observed over at least four runs with marginal loss inactivity due to handling error and isolation of FOL in pure form conﬁrmed by NMR and HPLC.Characterization of catalysts with several physico-chemical techniques (XRD, TEM, XPS, ICP, TPR) revealsthe presence of electron-rich Pt and ionic Co species in proximity with each other and these worksynergistically to facilitate maximum possible yield of FOL under ambient conditions and in water medium

Exploring thermocatalytic pyrolysis to derive sustainable chemical intermediates from plastic waste; role of temperature, catalyst, and reactor conditions - Venkataraghavan, R.; Bhure, Arvind; Khan, Tufeil Sartaj; Shikare, Dipak; Devi, R. Nandini; Dhepe, Paresh Laxmikant (Journal of the Indian Institute of Science, 2024)
Plastic waste is a growing concern globally on account of the increasing use of plastic worldwide, compounded by single-use applications, poor waste collection and management practices, and its consequent leakage into the environment. In addition, plastics are derived from non-renewable fossil resources, and their growing demand is also partly responsible for greenhouse gas emissions and climate change. The aim of this paper is to explore the potential of plastic waste as a material resource, and thermocatalytic pyrolysis as a recycling process, to produce aliphatic and aromatic hydrocarbons, which are important chemical intermediates for various industries. We show that plastic pyrolysis can achieve a high yield of liquid hydrocarbons (similar to 80%) with a suitable distribution of aliphatic and aromatic compounds, by using different pyrolysis conditions and a catalyst. Specifically, this paper demonstrates the possibility of deriving two key classes of hydrocarbons, i.e., aliphatic (C10-C20 hydrocarbons) and aromatic hydrocarbons (xylene, toluene and benzene derivatives) with a yield of similar to 80% liquid hydrocarbons via catalytic pyrolysis. We also briefly discuss the challenges and opportunities, and the environmental and economic implications.